Oil price volatility and its impact on economic growth and food security in Bangladesh: Oil price volatility and impact on growth and food security (Journal of the Bangladesh Agricultural University, 2018)
This study empirically examines oil price volatility and the impact of oil price changes on the growth of the economy and food security in Bangladesh. The study uses yearly data of macroeconomic variables from 1991 to 2015 and global food security index (GFSI) for the period 2012 to 2015. Furthermore, data of GFSI for previous four years have been simulated using exponential model. The GARCH (2, 1) model with minimum AIC postulates that volatility was high in the previous period and it has been continued to be lower in the current period (i.e. 2015). The co-integration test and error correction model exhibit that both in short-run and long-run case the increasing oil price negatively affected the growth of the economy. The simultaneous equations regression model using three-stage least squares estimator discloses that an increase in oil price declines the economic growth and food security simultaneously and significantly. Moreover, this study suggests that oil price volatility is not a good sign for the economy of Bangladesh, since, the country is an importer of crude oil, government policy should be quick responsive in relation to international oil market to create consistent oil market and sustainable economic development in Bangladesh.J. Bangladesh Agril. Univ. 16(3): 482–491, December 2018